The Conflict of a Mother in Her Family as Seen in Marsha Norman’s ‘Night Mother - Raflis Raflis; Anisa Amalia (Fakultas Sastra Universitas Ekasakti, 2018)
The problem in ‘Night, Mother is the external and internal conflict of mother in her family, the reason in choosing this topic is because the fact that drama shows the two sides that the mother has. On one side, the mother has to sacrifice everything in order to keep the family well, she has to show the role model that the kid can see in herself. However, on the other side, the mother also has the weakness, there are lots of burdens, and this can lead to the climax that she has fed up with her life, and she chooses to end it all.The purpose of this writing is the suffering on of modern mothers based on psychological analysis. It was divided into external conflict of disappointment from husband and son, internal conflict of suffering because of disease, and the conflict that leads to her suicide. This analysis uses psychological theory, Daiches said that psychological theory was based on the assumption that literary work always talks about human life events because it concerns about people and their lives, it must contain psychological aspects in the story. Psychology was expected to help us to know the characters well. In the method of research, qualitative method is used because Creswell said that it is attempted to trace the source of information in the form of document which were relevant to the object of the research. In finding in this analysis, this analysis will be focused on the psychological background of the character particularly the main character. First, the external conflict of disappointment from husband and son, Jessie feels lonely after her husband and son leave her. Second, internal conflict of suffering because of disease, the other factor that causes suffering to Jessie character is the disease that has become the trigger for her to commit suicide. Third, the conflict that leads to her suicide, Jessie as the mother is strong, however she needs support from her whole family, without that support, she feels dead inside and finally chooses to commit suicide. The problems faced by modern woman are loneliness, instable family structure, and crisis in emotionality.